A chromosomal inversion predicts the expression of sex steroid-related genes in a species with alternative behavioral phenotypes. (15th September 2019) - Grogan, Kathleen E.; Horton, Brent M.; Hu, Yuchen; Maney, Donna L.
Abstract: In white-throated sparrows, a chromosomal rearrangement has led to alternative phenotypes that differ in sex steroid-dependent behaviors. The rearrangement has captured the genes estrogen receptor alpha and 5-alpha reductase, making these genes strong candidates for mediating the behavioral phenotypes. We report here that of the two genes, expression of estrogen receptor alpha mRNA differs between the morphs and predicts behavior to a much greater extent than does expression of 5-alpha reductase mRNA. Differentiation of estrogen receptor alpha, therefore, is likely more important for the behavioral phenotypes. We also found that in some brain regions, the degree to which testosterone treatment affects the expression of steroid-related genes depends strongly on morph. A large morph difference in estrogen receptor alpha mRNA expression in the amygdala appears to be independent of plasma testosterone; this difference persists during the non-breeding season and is detectable in nestlings at post-hatch day seven. The latter result suggests a substrate for organizational effects of hormones during development. Highlights: A chromosomal rearrangement has led to alternative phenotypes that differ in sex steroid-dependent behaviors. We quantified the expression of four sex steroid-related mRNAs in the brain using in situ hybridization and quantitative real-time PCR. Of these genes, only estrogen receptor alpha was correlated with behavior. A large morph difference in estrogen receptor alpha in the amygdala emerges early during development and persists during the non-breeding season. Regulatory variation in estrogen receptor alpha may have contributed to the evolution of alternative behavioral phenotypes.